Characteristics and seasonal variation of organic matter in PM2.5 at a regional background site of the Yangtze River Delta region, China. (December 2015) - Feng, Jialiang; Hu, Junchao; Xu, Binhua; Hu, Xiaoling; Sun, Peng; Han, Wenliang; Gu, Zeping; Yu, Xiangming; Wu, Minghong
Abstract: One hundred and ten seasonal PM2.5 samples were collected at Lin'an (LA), a regional background site in the Yangtze River Delta (YRD) region of China, to study the chemical composition, seasonal variation and sources of carbonaceous aerosols in the YRD region. Concentrations of organic carbon (OC), elemental carbon (EC), water-soluble organic carbon (WSOC) and composition of solvent-extractable organic compounds (SEOC) including n -alkanes, hopanes, PAHs, n -fatty acids and levoglucosan were analyzed. Back trajectory and potential source contribution function (PSCF) analysis were conducted to identify the possible source areas of PM2.5 at LA. PM2.5 concentration at LA ranged from 15.7 μg m −3 to 182.1 μg m −3, with an annual average of 59.7 μg m −3 . A large part of the total carbon (OC + EC, 11.8 μg m −3 ) was water-soluble (42% in winter and spring, 56% in summer and 49% in autumn). SEOC concentration showed distinct seasonal variation of higher in winter and lower in summer. The average concentrations of n -alkanes and PAHs in winter (105 ng m −3 and 55 ng m −3 respectively) were 5 and 8 times of that in summer. Diagnostic ratios of PAHs and PSCF analysis suggested that vehicle emission was not the main source of PAHs at LA. Based on the levoglucosan concentration (annual average of 136 ng m −3 ), more than 15% of the OC at LA was from biomass burning. This data set provides useful information for the understanding of the characteristics of PM2.5 in the YRD region. Highlights: Characters and sources of organics in PM2.5 at LA, a regional background site in YRD were investigated. High pollution level was found at LA due to the regional anthropogenic activities. Distinct seasonal variations of concentration and composition of SEOC were observed. Vehicle emissions should not be the main source of PAHs in PM2.5 in YRD.